INTEGRATING DIGITAL TRANSFORMATION IN ENTERPRISE MANAGEMENT: ENHANCING EFFICIENCY AND COMPETITIVE ADVANTAGE - Abdisharipova Akljan Ismailovna (Scholar Express Journals, 2024)
Digital transformation is fundamentally reshaping the landscape of enterprise management, fostering efficiencies and driving competitive advantage. By adopting advanced technologies like artificial intelligence, big data analytics, and cloud computing, organizations are innovating and optimizing their processes. This article delves into the integration of digital transformation within enterprise management, exploring how digital tools improve operational efficiency, support data-driven decision-making, and enhance customer engagement. An in-depth analysis highlights the benefits, challenges, and strategies for successful digital transformation, positioning companies to thrive in a highly competitive and rapidly evolving business environment.
Keywords: Digital transformation; enterprise management; operational efficiency